A Morte de Maria Theresia.relatada por Dona Leonor de Almeida Portugal. Um olhar português sobre a soberania feminina - Anastacio, Vanda (Revista de Escritoras Ibéricas, 2017)
This article takes as a point of departure a letter, published here for the first time, written in Viena in 1780, by Leonor de Almeida Portugal (1750-1839), who was then Countess of Oeynhausen and would later became the 4rth Marchioness of Alorna. In this document, Leonor de Almeida describes the death of Empress Maria Theresia of Habsburg. The analysis of the letter and of the context in which it was written, suggest the existence of an underlying political agenda consisting in the legitimation of the presence of a woman in the Portuguese throne by publicizing the image of the Austrian Empress as a role model.